Ethical Issues in the Qualitative Researcher—Participant Relationship - Eide, Phyllis (Nursing ethics, 2008)
Qualitative research poses ethical issues and challenges unique to the study of human beings. In developing the interpersonal relationship that is critical to qualitative research, investigator and participant engage in a dialogic process that often evokes stories and memories that are remembered and reconstituted in ways that otherwise would not occur. Ethical issues are raised when this relationship not only provides qualitative research data, but also leads to some degree of therapeutic interaction for the participant. The purpose of this article is to examine some of the controversies inherent in the researcher's dilemma when this occurs, set within the context of a nursing caring theory (Swanson), and the International Council of Nurses Code of ethics for nurses, which provides guidance on global nursing practice.